Material management in high rise building / Muhammad Amar Adam Azlan and Nadira Ahzahar - Azlan, Muhammad Amar Adam; Ahzahar, Nadira (2023)
Material management plays a critical role in the successful execution of high-rise building projects. Efficient management of materials is essential to ensure timely project completion, cost optimization, and quality control. This paper aims to provide an overview of material management practices in high-rise buildings, highlighting their importance and challenges. Through a comprehensive analysis of current practices, the abstract discusses various aspects of material management, including inventory management, procurement, logistics, quality control, waste management, and material handling. It emphasizes the significance of accurate inventory keeping, cost optimization, enhanced quality control, improved safety, and better project planning in achieving successful outcomes. The abstract also explores the challenges faced in material management, such as storage limitations, procurement issues, skilled labour shortages, transportation constraints, and material shortages. Furthermore, potential solutions and recommendations are presented to address these challenges and enhance material management practices in high-rise buildings. These abstract aims to provide valuable insights for stakeholders involved in high-rise construction, enabling them to improve material management efficiency and overall project success.